Vegetation Pattern and Regeneration Dynamics of the Progressively Declining Monotheca buxifolia Forests in Pakistan: Implications for Conservation - Fayaz Ali (10934227) (2022)
Monotheca buxifolia (Falc.) A. DC., a wild edible fruit-yielding tree species, has economic and ecological importance, yet there is a lack of studies concerning its distribution pattern and regeneration dynamics at a larger-scale. This study aims to produce the first country-level classification of Monotheca forests based on their unique floristic composition and influential abiotic factors, besides their natural regeneration dynamics, across the environmentally diverse landscapes in Pakistan. For this purpose, floristic inventory was carried out in 440 plots where environmental variables, stand dendrometric characteristics and woody-species regeneration were recorded. During this survey, 3789 individuals of 27 woody tree species belonging to 25 genera and 22 families were sampled. These native and exotic tree species were mostly dicot (73%) with predominately mega-phanerophytic (88%) lifeforms, which largely reflect strong chorological differentiation and distinct linkage (55%) to the Sino-Japanese phytogeographical region. M. buxifolia and co-occurring species exhibiting similar environmental affinities were grouped into four ecologically distinct communities by Ward’s cluster analysis. Ordinations further highlight the special effects of topographic and edaphic factors besides anthropogenic interference on the sampled plots. Generally, Monotheca stands were moderately dense, with the average density varying considerably, ranging from 296 to 325 individuals/ha, with basal area ranging from 41.26 to 93.35 m2 ha−1. In the understory stratum, natural regeneration of Monotheca was mostly scant and mainly covered by Dodonaea shrubs. Size class structure of the dominant species shows pronounced effect of anthropogenic intervention as reflected by the presence of fewer individuals of juveniles and larger trees. Overall, the cut stump frequency was higher at juvenile and mature stages, which may be attributed to over-harvesting and extraction of fuelwood apart from the adverse effect of climate change in the region. We concluded that both topographic and edaphic factors coupled with biotic interventions are more influential in the distribution and persistence of M. buxifolia and co-occurring woody species and might be considered in its restoration and conservation. Thus, we recommend an urgent management plan to favor Monotheca regeneration for allowing the renewal of these rapidly declining remnant stands in Pakistan. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su14106111 Disclaimer: The University of Doha for Science and Technology replaced the now-former College of the North Atlantic-Qatar after an Amiri decision in 2022. UDST has become and first national applied University in Qatar; it is also second national University in the country.